1988
DOI: 10.1177/019459988809900503
|View full text |Cite
|
Sign up to set email alerts
|

Deep Spread Patterns in CT Staging of T2–4 Squamous Cell Laryngeal Carcinoma

Abstract: In addition to clinical examination and less sophisticated radiographic techniques, high-resolution computerized tomography (CT) can help to stage squamous cell carcinoma of the larynx. This study was undertaken to identify findings on CT scans that might predict the likelihood of radiation therapy (RT) alone, controlling the primary site disease without significant irradiation-related complications. Of 30 patients with T2-4 cancers of the larynx, 13 were classified as favorable and 17 were classified as unfav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Controversy exists regarding the association between CT-depicted cartilage involvement in laryngeal carcinoma and poor outcomes after radiation therapy for locally advanced head and neck cancer [13,14]. Although clinical evidence of cartilage involvement has historically been considered a contraindication for organ preservation with radiation therapy, more recent studies have suggested that cartilage abnormalities on CT or MRI are not an independent predictor of local failure [15][16][17][18].…”
Section: B LI M Bobinski R Gandour-edwards Et Almentioning
confidence: 99%
“…Controversy exists regarding the association between CT-depicted cartilage involvement in laryngeal carcinoma and poor outcomes after radiation therapy for locally advanced head and neck cancer [13,14]. Although clinical evidence of cartilage involvement has historically been considered a contraindication for organ preservation with radiation therapy, more recent studies have suggested that cartilage abnormalities on CT or MRI are not an independent predictor of local failure [15][16][17][18].…”
Section: B LI M Bobinski R Gandour-edwards Et Almentioning
confidence: 99%
“…The selection of patients with advanced (T3, T4) resectable laryngeal cancers for definitive radiotherapy based on favorable prognostic characteristics has resulted in reports with local control rates comparable to those reported in surgical series [25][26][27]. Unfavorable characteristics for definitive radiotherapy include soft tissue invasion [28], cartilage invasion [25,28,29], the need for tracheotomy [25,30,31], extension into the hypopharynx [32], extensive involvement of the preepiglottic space [26,33], infiltrative rather than exophytic growth [34][35][36][37], extension into the oropharynx, and base of tongue involvement [26]. Most of these characteristics directly reflect the tumor volume.…”
Section: Definitive Radiotherapymentioning
confidence: 99%
“…Contrary to the data of Harwood [31], Castelijns et al [5] observed a local failure rate of 63% in patients with signs of cartilage invasion by magnetic reso nance tomography (60% in Tl/2!). Freeman et al [17] and Isaacs et al [35] analyzed the computerized tomographies of patients irradiated for T2-4 supraglottic cancers and found a local control rate of 82% for a tumor volume of <6 cm3 versus 55% in tumors of >6 cm3. An additional unfavorable sign was deep infiltration of the base of the tongue.…”
Section: Advanced Laryngeal Cancer T3/4 N0/+mentioning
confidence: 99%